The cartilage degradation marker, urinary CTX-II, is associated with the risk of incident total joint replacement in postmenopausal women. A 18 year evaluation of the OFELY prospective cohort. Issue 4 (April 2020) - Garnero, P.; Sornay-Rendu, E.; Chapurlat, R.
Summary: Objective: Identifying objective risk-indicators for total joint replacement (TJR) is useful to enrich population at high risk in OA clinical trials. We investigate the association of urinary CTX-II, a biochemical marker of cartilage breakdown, with the risk of TJR. Method: 478 postmenopausal women (mean age 65.5 ± 7.5 yr) from the OFELY cohort were studied. CTX-II, serum CTX-I (bone resorption) and PINP (bone formation), were measured at baseline. Association between CTX-II and incidence of TJR was assessed by Cox Hazard Regression. Results: During a median (95%CI) 17.8 (15.0–18.1) years follow-up, 38 women sustained a TJR, including hip ( n  = 29) or knee ( n  = 9) replacement. CTX-II -but not CTX-I or PINP- was higher in patients with TJR (+34%, P  = 0.001 vs women with no TJR). Increased baseline CTX-II levels were associated with a higher risk of TJR with a Hazard Ratio (HR) (95 CI) of 1.45 (1.13–1.85) per 1 SD increase after adjustment for age, BMI and total hip BMD. CTX-II remained significantly associated with the risk of TJR after further adjustment for total WOMAC, prevalent knee OA (KL ≥ 2) and self-reported hip OA [HR (95 CI): 1.31 (1.01–1.71), P  = 0, 04]. When women were categorized as low and high CTX-II (lower and above the 95 percentile of healthy premenopausal women, respectively), subjects with high levels had an age-BMI-hip BMD adjusted HR (95 CI) of 3.00 (1.54–5.85) compared to women with low levels which remained significant after further adjustment for WOMAC, knee and/or hip OA [HR (95 CI): 2.45 (1.25–4.89), P  = 0.01]. Conclusion: CTX-II is an independent risk indicator of TJR in postmenopausal women suggesting that it may be useful to identify subjects at high risk of TJR.